Juridical Study on the Legal Certainty of Notary Electronic Deeds in the Covid-19 Pandemic - Sa'atun, Siti; Argo Victoria, Ong (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2021)
The purpose of this study was to find out that guarantees of protection of property rights are realized through the making of an authentic deed. The important position of an authentic deed is based on the function of the authentic deed. An authentic deed has 2 (two) important functions, namely the deed as a formal function which means that a legal act will be more complete if a deed is made. The function of the instrument of evidence is the deed as a means of proof in which the deed is made by the parties bound by an agreement for the purpose of proof. The method used in this writing is the normative method. Normative Law Research is legal research conducted by examining literature or secondary data. The conclusion of this study explains that the Terms are set out in Article 28 Regelemet op het Notaris-ambt in Indonesia (Ordinance 11 January 1860) and Article 16 paragraph (1) letter m of Act No. 30 of 2004 Jo. Act No. 2 of 2014 Concerning the Notary Office. The entry of Covid-19 virus in the country is a matter of its own for the implementation of these conditions. Therefore the legal certainty of the validity of the Electronic Deed must be regulated in more detail and have binding legal force.